Development of mobile electron beam plant for environmental applications. (July 2016) - Han, Bumsoo; Kim, Jinkyu; Kang, Wongu; Choi, Jang Seung; Jeong, Kwang-Young
Abstract: Due to the necessity of pilot scale test facility for continuous treatment of wastewater and gases on site, a mobile electron beam irradiation system mounted on a trailer has developed. This mobile electron beam irradiation system is designed for the individual field application with self-shielded structure of steel plate and lead block which will satisfy the required safety figures of International Commission on Radiological Protection (ICRP). Shielding of a mobile electron accelerator of 0.7 MeV, 30 mA has been designed and examined by Monte Carlo technique. Based on a 3-D model of electron accelerator shielding which is designed with steel and lead shield, radiation leakage was examined using the Monte Carlo N-Particle Transport (MCNP) Code. Simulations with two different versions (version 4c2 and version 5) of MCNP code showed agreements within statistical uncertainties, and the highest leakage expected is 5.5061×10 −01 (1±0.0454) μSv/h, which is far below the tolerable radiation dose limit for occupational workers. This unit could treat up to 500 m 3 of liquid waste per day at 2 kGy or 10, 000 N m 3 of gases per hour at 15 kGy. Highlights: A mobile electron beam irradiation system mounted on a trailer has developed. It is designed for treatment of wastewater and flue gas on site. Shielding of 0.7 MeV, 30 mA accelerator has done by a Monte Carlo technique. It can treat up to 500 m 3 /d of liquid waste at 2 kGy or 10, 000 N m 3 /h of gas at 15 kGy.